Stroke Treatment With PAR-1 Agents to Decrease Hemorrhagic Transformation - Lyden, Patrick D.; Pryor, Kent E.; Minigh, Jennifer; Davis, Thomas P.; Griffin, John H.; Levy, Howard; Zlokovic, Berislav V. (Frontiers in Neurology, 2021)
Ischemic stroke is the most widespread cause of disability and a leading cause of death in developed countries. To date, the most potent approved treatment for acute stroke is recanalization therapy with thrombolytic drugs such as tissue plasminogen activator (rt-PA or tPA) or endovascular mechanical thrombectomy. Although tPA and thrombectomy are widely available in the United States, it is currently estimated that only 10–20% of stroke patients get tPA treatment, in part due to restrictive selection criteria. Recently, however, tPA and thrombectomy selection criteria have loosened, potentially allowing more patients to qualify. The relatively low rate of treatment may also reflect the perceived risk of brain hemorrhage following treatment with tPA. In translational research and a single patient study, protease activated receptor 1 (PAR-1) targeted therapies given along with thrombolysis and thrombectomy appear to reduce hemorrhagic transformation after recanalization. Such adjuncts may likely enhance the availability of recanalization and encourage more physicians to use the recently expanded selection criteria for applying recanalization therapies. This narrative review discusses stroke therapies, the role of hemorrhagic transformation in producing poor outcomes, and presents the data suggesting that PAR-1 acting agents show promise for decreasing hemorrhagic transformation and improving outcomes.